Aid worker adaptability in humanitarian operations: Interplay of prosocial motivation and authoritarian leadership - Mojtaba Salem; Niels Van Quaquebeke; Maria Besiou (Production and Operations Management, 2022)
Many field office leaders contend that authoritarian leadership improves the performance of humanitarian operations. The common narrative is that authoritarian leadership helps aid workers more quickly adapt to changes and thus deliver better job performance (e.g., by improving operations in their field office). However, given that field reports often highlight extant leadership as the source of serious operational failures, could leaders with an authoritarian style be part of the problem? We draw on psychological theorizing on the nature of human motivation to address this question. Specifically, we note that many aid workers primarily join humanitarian operations with the prosocial motive to help beneficiaries. While proactive adaptability is inherent to prosocial motivation, we hypothesize that authoritarian leadership may curtail the relationship by impeding aid workers' autonomy. We find support for our theorizing in a sample of 299 humanitarian aid workers from the field. Additionally, we conducted 31 expert interviews to contextualize and validate our empirical findings. The paper concludes by discussing the findings' theoretical and managerial implications for humanitarian operations.
Keywords: 650; adaptability; authoritarian leadership; humanitarian operations; prosocial motivation